Advantages and Disadvantages of the Use of L1 in Basic English - Granados, Anuar (CIEX JOURNAL, 2016)
Krashen, S. (1995) states: the language learning process accelerates when students are provided by comprehensible input in the target language. The objective of this presentation is to identify the advantages and disadvantages of using Spanish in the EFL classroom. The participants were: a teacher and 5 students. The instruments include interview guides to the teacher and students and a class observation format. The results revealed that: the teacher felt forced to use the students’ L1 for: instructions and activities.